Makna Ritual Fangasi Sebagai Upacara Adat Setelah Kematian Suku Nias di Desa Ononazara Kecamatan Tugala Oyo Kabupaten Nias Utara Tahun 2024 - Ratna Zebua; Robert Juni Tua Sitio; Elvri Teresia Simbolon; Roida Lumbantobing; Yulia Kurnia Sari Sitepu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The aim of the research is to find out the meaning of the fangasi ritual as a traditional ceremony after the death of the Nias tribe in Ononazara village, Tugala Oyo subdistrict, North Nias district. The research method used in this research is descriptive qualitative research about the meaning of the fangasi ritual as a traditional ceremony after the death of the Nias tribe in Ononazara village, Tugala Oyo subdistrict, North Nias district. The result of this research is that the meaning of the fangasi ritual is the highest form of respect that the Nias tribe has for every person's life. The meaning of the fangasi ritual in Ononazara village is the last event for the person who has died. The fangasi ritual is carried out depending on its position in custom and also as a form of a child's obligation to his parents who have died with the aim of paying off the debts of his parents or the person who died while he was alive in the world. It can be concluded that the meaning of the fangasi ritual is a traditional ceremony implemented in the village of Ononazara, which is passed down from generation to generation, which aims to resolve the burden on the family of the deceased as a sign of final respect, and so that the spirits of the deceased will rest in peace.